2022
DOI: 10.1002/jat.4321
|View full text |Cite
|
Sign up to set email alerts
|

Serum‐derived exosomes from SD rats induce inflammation in macrophages through the mTOR pathway

Abstract: Inhalation of beryllium and its compounds can cause lung injuries, resulting from inflammation and oxidative stress. Multivesicular bodies (MVB), such as exosomes, are membrane vesicles produced by early and late endosomes that mediate intercellular communications. However, the role of exosomes in beryllium toxicity has not been elucidated. This current study aimed to investigate the functional role of exosomes in lung injury resulting from beryllium sulfate (BeSO 4 ). Here, Sprague-Dawley (SD) rats were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…24 While another study showed that rat-derived serum-Exo inhibits macrophage inflammation. 25 This study found that serum-Exo from healthy donors was efficiently internalized by macrophages. Newly formed blood vessels play an important role in bone regeneration via osteogenesis-angiogenesis coupling.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…24 While another study showed that rat-derived serum-Exo inhibits macrophage inflammation. 25 This study found that serum-Exo from healthy donors was efficiently internalized by macrophages. Newly formed blood vessels play an important role in bone regeneration via osteogenesis-angiogenesis coupling.…”
Section: Discussionmentioning
confidence: 79%
“… 24 While another study showed that rat‐derived serum‐Exo inhibits macrophage inflammation. 25 This study found that serum‐Exo from healthy donors was efficiently internalized by macrophages. Moreover, serum‐Exo treatment alleviated LPS‐induced macrophage inflammation in vitro.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation